Images of Captivity, Water and Inertia in Fernanda Trías’ Mugre rosa - Cannavacciuolo, Margherita (Oltreoceano - Rivista sulle migrazioni, 2024)
The present article considers the novel Mugre rosa (2020) by the Uruguayan writer Fernanda Trías, with the purpose of analyzing the relationship between water and the constellation of images of captivity that is articulated in the text. Translated into Italian in 2022 by Editorial Sur as Melma rosa, the novel has been awarded the Sor Juana Inés de la Cruz Prize at the Guadalajara International Book Fair (FIL) in 2021 and has established its author as one of the best writers of their generation. In the novel ‒whose publication coincides with the covid-19 pandemic, which makes us think about the anticipatory power of literature‒ a mysterious transformation of the ecosystem of an unnamed world and water pollution triggers an epidemic, and the narration revolves around the protagonist’s attempts to survive in this state of affairs in a continuous coming and going of memory between the past and the present. The woman then finds herself divided between the memorial flight and the impossibility of leaving the city to seek a better future. It will be seen how the contaminated water of the sea and rivers constitutes a symbolic framework linked both with intimacy (Bachelard [1942] 2005) and the inertia of the characters, at the same time as with the death of the natural environment (Libis [ 1996] 2004). In particular, the most forceful line of the narrative device will be considered; that is, captivity. The range of variations in which the confinement is declined will be the specific object of analysis starting from and through the reflection on the aquatic isotopy that is constructed in the story, as well as on the deadly nuance that the water acquires. The next step is the consideration of the correspondence established between the articulation of the aquatic space and the construction of the characters ‒since the text implicitly reflects on the distance that separates the subject from others and even from himself and his own desire‒, as well as about memory and remembrance that arise as an attempted response and reaction to the state of inertia in which the protagonist finds herself.